Insights into Redox Dynamics of Vanadium Species Impregnated in Layered Siliceous Zeolitic Structures during Methanol Oxidation Reactions - Vieira, Luiz H. [UNESP]; Possato, Luiz G. [UNESP]; Chaves, Thiago F. [UNESP]; Lee, Jason J.; Sulmonetti, Taylor P.; Jones, Christopher W.; Martins, Leandro [UNESP] (Wiley, 2020)
Supported transition metal catalysts have been extensively applied to oxidative and reductive processes. The understanding of surface speciation and active site-support interactions in these materials play a substantial role in developing improved heterogeneous catalysts. Herein, a series of impregnated 3D ferrierite and 2D ITQ-6 siliceous supports with variable loading of vanadium oxide was prepared. Chemical and structural properties of the materials were studied by X-ray diffraction, N2 physisorption, inductively coupled plasma – optical emission spectrometry, X-ray absorption, Fourier transform infrared and diffuse reflectance UV-vis spectroscopies, and temperature-programmed reduction with H2. Reactivity of the catalyst surface, associated with the incidence of isolated silanol groups, was found to be more effective when vanadium oxides were better dispersed and stabilized than increases in surface area. Differences in activation and the oxidation state dynamic behavior of active sites were then probed by methanol oxidation as a model reaction monitored by in situ FTIR spectroscopy and XANES/MS. By applying isothermal periods of reaction under non-oxidizing atmosphere and regeneration of catalysts by O2, it was found that, even at distinct rates, all types of sites are accessible during reaction, since a complete reduction to V4+ was observed. However, reoxidation of sites to V5+ is limited and sensitive to the different vanadium species on the surface, and probably, the determinant factor of the distinct V5+/V4+ equilibrium reached for the catalysts when the reaction is carried out under constant oxidizing atmosphere.
Keywords: lamellar material; methanol; oxidation; vanadium; zeolite structure